2015
DOI: 10.1111/asj.12432
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet distribution of immature canine oocytes in relation to their size and the reproductive stage

Abstract: This study investigated the distribution of lipid droplets (LD) in immature canine oocytes in relation to their size and the reproductive stage. Oocytes were collected from the ovaries of bitches at different estrous stages, divided according to their size (110-120 µm; >120 µm), and stained with Nile Red to detect lipid droplet distribution. At the follicular phase most of the oocytes displayed a diffuse pattern of LD distribution, whereas at anestrus and luteal phase oocytes showed LD mainly in a peripheral/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Triglycerides are an important storage form of energy, which mainly exist in the form of lipid droplets. Though the content of lipid droplets varies greatly among different species and developmental stages, mammalian oocytes are generally rich in lipids to ensure sufficient energy supply for meiosis ( Genicot et al, 2005 ; Ariu et al, 2016 ; Abazarikia et al, 2020 ).…”
Section: Triglyceride Breakdownmentioning
confidence: 99%
“…Triglycerides are an important storage form of energy, which mainly exist in the form of lipid droplets. Though the content of lipid droplets varies greatly among different species and developmental stages, mammalian oocytes are generally rich in lipids to ensure sufficient energy supply for meiosis ( Genicot et al, 2005 ; Ariu et al, 2016 ; Abazarikia et al, 2020 ).…”
Section: Triglyceride Breakdownmentioning
confidence: 99%
“…Canid oocytes contain a large amount of cytoplasmic lipids compared to other mammalian species [74]. Lipid yolk bodies first appear in the cytoplasm of the primary oocyte and the amount of these lipid bodies increases throughout the entire process of oogenesis, giving its dark appearance which is distinct from that of other mammalian species [75][76][77][78][79][80]. Analysis of total lipids extracted from dogs of various breeds revealed that intracellular lipids include saturated fats, triglyceride, cholesterol, phospholipids, and glycolipid, and that types and amounts of lipid fractions are consistent among individuals within and between different breeds [77].…”
Section: Gametogenesis and Embryogenesismentioning
confidence: 99%
“…Analysis of total lipids extracted from dogs of various breeds revealed that intracellular lipids include saturated fats, triglyceride, cholesterol, phospholipids, and glycolipid, and that types and amounts of lipid fractions are consistent among individuals within and between different breeds [77]. However, the distribution of lipid bodies varies among oocytes recovered from different reproductive stages [78]. Specifically, oocytes recovered during the follicular phase displayed a diffuse pattern of lipid bodies while those retrieved during anestrus or luteal period exhibited peripheral or perinuclear distribution [78].…”
Section: Gametogenesis and Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…В следующей серии экспериментов представлены данные о типах локализации липидных гранул в интактных и прокультивированных с наночастицами ВДК (или в их отсутствии) ооцитов, диагностированных после ВСВ-теста, как растущие или завершившие фазу роста in vivo. Анализ локализации липидных гранул, визуализированных флуоресцентным зондом Nile red, проводили в соответствии с классификацией, представленной в работе Ariu F. с соавторами [13]. Визуализированы следующие типы локализации (распределения) липидных гранул: хаотичная (неравномерное расположение по всей ооплазме), диффузная (равномерное расположением липидных капель в цитоплазме) и периферийно-перинуклеарная (периферийное и околоядерное распределение) локализация (рис.…”
Section: Based On the Visualization By The Fluorescent Probe (Nile Reunclassified